Gestational hypoxia modulates expression of corticotropin‐releasing hormone and arginine vasopressin in the paraventricular nucleus in the ovine fetus - Myers, Dean A. (Physiol Rep, 2016)
Maturation of the fetal hypothalamo–pituitary–adrenocortical (HPA) axis is critical for organ maturation necessary for the fetus to transition to the ex‐utero environment. Intrauterine stressors can hasten maturation of the HPA axis leading to fetal growth restriction and in sheep, premature birth. We have previously reported that high‐altitude mediated, long‐term‐moderate gestational hypoxia (LTH) during gestation has a significant impact on the fetal HPA axis. Significant effects were observed at the level of both the anterior pituitary and adrenal cortex resulting in elevated plasma ACTH during late gestation with decreased adrenocortical expression of enzymes rate limiting for cortisol synthesis. As such, these fetuses exhibited the normal ontogenic rise in fetal plasma cortisol but an exaggerated cortisol response to acute stress. This study extended these findings to ACTH secretagogue expression in the PVN using in situ hybridization. We report that the expression of AVP but not CRH was increased in the medial parvocellular PVN (mpPVN) in the LTH fetus. This represented an increase in both AVP mRNA per neuron as well as an increase in AVP hybridizing neurons with no increase in mpPVN CRH neurons. LTH had no effect on PVN volume, area of CRH or AVP hybridization, thus LTH did not have a trophic effect on the size of the nucleus. In conclusion, there appears to be a switch from CRH to AVP as a primary ACTH secretagogue in response to LTH, supporting our previous findings of increased anterior pituitary sensitivity to AVP over CRH in the LTH fetus.